2010
DOI: 10.1111/j.1365-2265.2010.03875.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgical treatment for nonfunctioning pituitary adenomas: a systematic review and meta‐analysis

Abstract: Observational evidence supports the association between a combined approach of transsphenoidal surgery with radiotherapy and improvements in visual field defects and reduction in tumour recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
3
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 53 publications
3
77
3
6
Order By: Relevance
“…Furthermore, the risk of tumor recurrence was higher in patients with residual tumor and in those who did not receive radiotherapy (13,14). A meta-analysis also showed that lack of radiotherapy after initial pituitary surgery was associated with an increased risk of tumor recurrence surgery (18). In addition, high Ki-67 and TUNEL labeling indices, as well as the expression of phosphoAkt, phospho-p44/42 MAPK, and PTTG1, were associated with NFPA recurrence, although that study assessed those cell proliferation markers in only 35 patients with NFPA (20).…”
Section: █ Discussionmentioning
confidence: 92%
“…Furthermore, the risk of tumor recurrence was higher in patients with residual tumor and in those who did not receive radiotherapy (13,14). A meta-analysis also showed that lack of radiotherapy after initial pituitary surgery was associated with an increased risk of tumor recurrence surgery (18). In addition, high Ki-67 and TUNEL labeling indices, as well as the expression of phosphoAkt, phospho-p44/42 MAPK, and PTTG1, were associated with NFPA recurrence, although that study assessed those cell proliferation markers in only 35 patients with NFPA (20).…”
Section: █ Discussionmentioning
confidence: 92%
“…Certain studies reported improved pituitary function following surgery [36] whereas others did not mention any change or else reported deterioration.…”
Section: Nonfunctioning Macroadenomamentioning
confidence: 95%
“…63 In studies without iMRI use, the incidence of postoperative ophthalmological symptoms worsening was reported to range from 0% to 4%. 7,21,39,47 Nevertheless, due to patient and tumor characteristic variations, a direct comparison is prone to be biased.…”
Section: 21mentioning
confidence: 99%